How to Chemigate Salinity-Stressed Plants with Hydrogen Peroxide to Increase Survival and Growth Rates - Guodong Liu; Yuncong Li; Kimberly Moore; Kim Gabel; Lei Wu; Rafael Muñoz-Carpena (EDIS)
Man-made activities can induce climate change and global sea-level rise, posing threats to the survival and growth of coastal vegetation in Florida. This 3-page fact sheet explains how to ensure plant survival and facilitate the growth of coastal vegetation threatened by sea-level rise and the resulting oxygen deficiencies and saline stresses. Written by Guodong Liu, Yuncong Li, Kimberly Moore, Kim Gabel, Lei Wu, and Rafael Muñoz-Carpena, and published by the Horticultural Sciences Department, April 2016.